Cancer survivorship in low-middle income countries - Does quality of life matter? - Syed, Binafsha Manzoor (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
Cancer survivorship has improved in the recent years due to screening facilities, modernized treatment options and advanced cancer care in specialized centers globally. However, in low-middle-income countries cancer survivorship is not yet improved to that stature. There are multifaceted issues including delay in diagnosis, financial burden and in certain situations in appropriate treatment creates long term effects not only on patients but also on their families. Multidisciplinary approach is a limitation in the LMIC and the mental health aspects are least studies in cancer survivors. Therefore, a revised more focused and evidence based management plan along with long term quality of life issues needs to be focused in patients from LMIC.